Control groups in experimental research: particularities in clinical trials - Javier Cruz Rodríguez; María Margarita Ríos Cabrera (Medisur)
Experimentation is a routine activity of utmost importance for the development of humanity and with high significance, especially in clinical trials. Inaccuracies in the use of control groups have been detect-ed in these studies. The purpose of this article is to expose the characteristics of these groups, while discussing some situations and errors in relation to their use, which are frequently made.